2012
DOI: 10.1016/j.ejpb.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface coating on the biodistribution profile of gold nanoparticles in the rat

Abstract: a b s t r a c tSuccessful application of gold nanoparticles (AuNPs) in biomedicine requires extensive safety assessment for which biokinetic studies are crucial.We evaluated the biodistribution of AuNPs ($20 nm) with different surface coatings: citrate, 11-MUA and 3 pentapeptides, CALNN, CALND and CALNS, after i.v. administration to rats (0.6-1 mg Au/kg). Biodistribution was evaluated based on Au tissue content measured by GFAAS.Citrate-AuNPs were rapidly removed from circulation with 60% of the injected dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
74
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 46 publications
(78 reference statements)
5
74
0
1
Order By: Relevance
“…However, in TEM images no difference in particle size was observed this might be due to measurement of only electron dense gold core in TEM analysis ( fig. 5) [22] . TEM micrograph of gold nanoparticles indicates that the gold nanoparticles were uniformly dispersed with spherical shape.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in TEM images no difference in particle size was observed this might be due to measurement of only electron dense gold core in TEM analysis ( fig. 5) [22] . TEM micrograph of gold nanoparticles indicates that the gold nanoparticles were uniformly dispersed with spherical shape.…”
Section: Resultsmentioning
confidence: 99%
“…Citrate-AuNPs were synthesized using HAuCl 4 and sodium citrate according to the Turkevich method [21][22] . Briefly, 50 ml of 0.58 mM HAuCl 4 was boiled in a conical flask under continuous stirring, 1 ml of 52.6 mM sodium citrate was added and heated for another 15 min.…”
Section: Synthesis Of Citrate-reduced Gold Nanoparticles (Citrate-aunmentioning
confidence: 99%
“…3, 4 Morais et al 5 evaluated the biodistribution of 20 nm gold nanoparticles (GNPs) with six different surface coatings and demonstrated that GNPs are rapidly distributed, while liver is the preferential accumulation organ, with GNPs trapped in KCs, hepatocytes, and endosomes. Sadauskas et al 6 showed that GNPs, independent of size (2 and 40 nm), were taken up primarily by KCs in the liver and secondarily by macrophages at other sites.…”
mentioning
confidence: 99%
“…[34][35][36] In addition, many investigations reported that following parenteral administration, GNPs were detected in blood, lungs, heart, liver, spleen, stomach, small intestine, and kidneys. [37][38][39][40] Moreover, previous investigations showed that distribution of GNPs in tissue is size-dependent, 34,35 dose-dependent, 36 and surface charge-dependent. 37,38 Furthermore, James et al 41 examined the biodistribution of GNPs and demonstrated a high accumulation of GNPs in lung 4 hours, 14 days, 21 days, and 28 days following the single administration.…”
mentioning
confidence: 99%
“…[37][38][39][40] Moreover, previous investigations showed that distribution of GNPs in tissue is size-dependent, 34,35 dose-dependent, 36 and surface charge-dependent. 37,38 Furthermore, James et al 41 examined the biodistribution of GNPs and demonstrated a high accumulation of GNPs in lung 4 hours, 14 days, 21 days, and 28 days following the single administration. Previous data pointed that parenteral or oral administration of metals induces biosynthesis of metallothioneins (MTs).…”
mentioning
confidence: 99%